Opioids Are Infrequently Required following Ambulatory Otologic Surgery. Issue 9 (October 2021) - Mavrommatis, Maria A.; Fan, Caleb J.; Villavisanis, Dillan F.; Kaul, Vivian F.; Schwam, Zachary G.; Wong, Kevin; Perez, Enrique; Wanna, George B.; Cosetti, Maura K.
Abstract : Objective: To determine the frequency with which postoperative opioid prescriptions are required after ambulatory otologic surgery. Study Design: Retrospective chart review. Setting: Tertiary otology–neurotology practice. Patients: Patients (n = 447) given over-the-counter acetaminophen and ibuprofen following ambulatory otologic surgery between July 1, 2018 and June 30, 2020. Intervention: Opioid prescription upon request. Main Outcome Measures: Patient, disease, and surgical variables such as age, sex, past medical history, chronic pain condition, surgical procedure, primary versus (vs.) revision surgery, and endoscopic vs. microscopic approach were examined for relationship to ad hoc opioid prescription rate. Results: Of 370 adult patients (mean age 49.0 yrs, range 18.0–88.5 yrs), 75 (20.3%) were prescribed opioids for postoperative pain, most commonly oxycodone-acetaminophen 5/325 mg. Of 77 pediatric patients (mean age 8.8 yrs, range 0.7–17.9 yrs), 5 (6.5%) were prescribed postoperative opioid analgesia. In the adult population, chronic pain condition, pain medication use at baseline, canal wall up mastoidectomy, tympanoplasty, tympanomeatal flap, bone removal of the mastoid, postauricular incision, and intraoperative microscopy were independent predictors of opioid pain prescription. When controlling for all significant variables, only chronic pain condition remained significant (odds ratio = 3.94; p = 0.0007). In the pediatric population, atresiaplasty, meatoplasty, and conchal cartilage removal were independently associated with opioid prescription, but none remained significant when analyzed in a multivariate linear model. Conclusions: Pain following ambulatory otologic surgery may be adequately managed with over-the-counter pain medications in the majority of cases. Opioids may be necessary in adults with preexisting pain conditions.